The Multivalent Role of Fibronectin-Binding Proteins A and B (FnBPA and FnBPB) of Staphylococcus aureus in Host Infections - Speziale, Pietro; Pietrocola, Giampiero (Frontiers in Microbiology, 2020)
Staphylococcus aureus is one of the most important human pathogens, causing several infectious diseases including sepsis, pneumonia, osteomyelitis, endocarditis, skin and soft tissue infections. This pathogenicity is due to a variety of virulence factors including several cell wall-associated proteins (CWA). CWA proteins have modular structures with distinct domains binding different ligands. Most strains of S. aureus express two CWA related fibronectin (Fn)-binding adhesins FnBPA and FnBPB (Fn-binding proteins A and B), which are encoded by closely linked genes. The N-terminus of FnBPA and FnBPB comprises an A domain which binds ligands such as fibrinogen, elastin and plasminogen. The A domain of FnBPB also interacts with histones and this binding results in the neutralization of the antimicrobial activity of these molecules. The C-terminal moiety of these adhesins comprises a long, intrinsically disordered domain composed of 11/10 fibronectin-binding repeats. These repetitive motifs of FnBPs promote invasion of cells that are not usually phagocytic via a mechanism by which they interact with integrin 51 through a Fn mediated-bridge. The FnBPA and FnBPB A domains engage in homophilic cell-cell interactions and promote biofilm formation and enhance platelet aggregation. This review updates the current understanding of the molecular architecture and functional properties of FnBPs and the role that they play in the onset and progression of infections.